THE POTENTIAL EFFECT OF RED DRAGON FRUIT (Hylocereus polyrhizus) PEEL ETHANOL EXTRACT ON ENDOMETRIOSIS PROGRESSIVITY IN ENDOMETRIOSIS MICE - Anindya Hapsari; Yanuar Eka Pujiastutik (Jurnal Kedokteran Hewan, 2018)
The aim of this study was to know the effect of red dragon fruit (Hylocereus polyrhizus) peel ethanol extract at dose of 0.25, 0.5, and 1 mg/gbw on endometriosis progressivity, signed by granuloma, on mouse model of endometriosis. Twenty five female mice were used as samples anddivided into 5 groups: 1 positive control, 1 negative control, and 3 treatment groups. Positive control and treatment groups were induced as modelof endometriosis for 14 days. The next 14 days, placebo was given to both control groups, while red dragon fruit peel ethanol extract at dose of0.25, 0.5, and 1 mg/g bw were given to mice in treatment groups as much as 0.2 mL/25 g bw/day orally. Endometriotic lesion was examined.Result showed that there were significantly differences on granuloma among control groups and treatment groups. The conclusion was reddragon fruit peel ethanol extract could inhibit endometriosis progressivity, signed by granuloma, on mouse model of endometriosis.